Altered structural connectivity is related to attention deficit/hyperactivity subtypes: A DTI study - Ercan, Eyup Sabri; Suren, Serkan; Bacanli, Ali; Yazici, Kemal Utku; Calli, Cem; Ardic, Ulku Akyol; Rohde, Luis Augusto (Elsevier Ireland Ltd, 2016)
This study aimed to provide novel insights into the white matter (WM) microstructural properties of Attention Deficit/Hyperactivity Disorder (ADHD) subtypes by recruiting a relatively large sample of stimulant-naive children and adolescents who had no comorbidity other than Oppositional Defiant Disorder and were homogenous according to the DAT1 gene polymorphism. A sample of 72 ADHD subjects and 24 controls aged 8-15 years were enrolled in the study. We applied tract-based spatial statistics to the DTI measures for obtaining fractional anisotropy (FA) and axial, radial diffusivity (AD, RD) measures to explore ADHD type-related differences in WM for the whole brain. Comparing ADHD-Combined group (ADHD-C) with the ADHD predominantly inattentive group (ADHD-I) we detected increased RD in several bilateral brain area and increased AD mostly in left side of the brain, including the body and splenium of the corpus callosum; the anterior and posteriors limbs of the internal capsule; the superior, anterior and posterior corona radiata; the posterior thalamic radiation; and the superior longitudinal fasciculus. Likewise, mostly in the overlapping brain areas, the ADHD-C group presented increased AD values than ADHD-RI. Significant differences among ADHD types could be a preliminary evidence that they have distinct microstructural properties. There were no significant differences in diffusivity between controls and both the ADHD group as whole or any ADHD subgroups. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: ADHD; Imaging; DTI; White mater; Neuropsychology